The trustworthiness of reference group and cooperative quality: implications for online crowdsourcing market. (2015) - Li, Xiaoling; Tian, Qian; Yan, Hui; Li, Xinjian
Crowdsourcing is one emerging business model featured by value cooperation of focal agent and crowds. The trustworthiness of first movers, they act as reference groups, would provide referent information for crowds' decision. It is necessary to develop an understanding of the relationship of reference groups and the cooperative quality of crowd task. The authors argue that reference groups can obtain trustworthiness in the eyes of the crowd, such as integrity trustworthiness and ability trustworthiness. We examine the influence mechanism of trustworthiness of reference groups, and testify our arguments with secondary data from a typical crowdsourcing website. We found that, when the perceived risk of task is high, the effect of reference groups' integrity trustworthiness on crowds' participation is greater than ability trustworthiness. While the perceived risk is low, the effect of reference groups' ability trustworthiness on crowds' participation is greater than integrity trustworthiness. And the degree increase of the participation of crowd will improve cooperative quality between focal agent and qualified crowd. The paper supposes management policies based on the empirical research.